AI-MEDIATED LEARNING IN ADVANCED MATHEMATICS: HOW PRE-SERVICE TEACHERS DEVELOP EMERGING PEDAGOGICAL THINKING - Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto; Melda Jaya Saragih (ALGORITMA: Journal of Mathematics Education, 2026)
Abstract Since the use of artificial intelligence (AI) in education continues to broadly expand, understanding its role in pre-service teacher development has become increasingly important. This study explores how AI used in Advanced Mathematics courses contributes to the development of pedagogical thinking among pre-service mathematics teachers. A qualitative approach was employed involving 51 students. Data were collected through questionnaires and follow-up interviews, then analyzed using thematic analysis. The findings indicate that students use AI to support their understanding of abstract mathematical concepts and solve problems through simplified explanations and structured solution steps. Students’ engagement with AI is characterized by several tensions between efficiency and understanding, assistance and dependency, and ease of use and prompt accuracy. These tensions foster reflection, metacognitive awareness, and more critical use of AI. The findings also reveal the emergence of pedagogical thinking, although it remains limited in addressing learner diversity and the complexity of instructional contexts. Abstrak Seiring dengan semakin meluasnya penggunaan kecerdasan buatan (AI) dalam pendidikan, pemahaman mengenai perannya dalam perkembangan calon guru menjadi semakin penting. Penelitian ini bertujuan mengeksplorasi bagaimana penggunaan AI dalam mata kuliah matematika lanjut berkontribusi terhadap perkembangan pemikiran pedagogis mahasiswa calon guru matematika. Penelitian menggunakan pendekatan kualitatif dengan melibatkan 51 mahasiswa. Data dikumpulkan melalui kuesioner dan wawancara lanjutan, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa mahasiswa memanfaatkan AI untuk memahami konsep matematika abstrak dan menyelesaikan masalah melalui penjelasan yang lebih sederhana serta langkah-langkah yang terstruktur. Keterlibatan mahasiswa dalam penggunaan AI diwarnai oleh beberapa ketegangan antara efisiensi dan pemahaman, bantuan dan ketergantungan, serta kemudahan penggunaan dan ketepatan prompt. Ketegangan tersebut mendorong refleksi belajar, kesadaran metakognitif, dan penggunaan AI yang lebih kritis. Temuan juga menunjukkan munculnya pemikiran pedagogis, meskipun masih terbatas dalam mempertimbangkan keragaman peserta didik dan kompleksitas situasi pembelajaran.